Analysis of the Cost Budget Plan Requirements for the Construction of Ketegan Village Office, Pasuruan - Moh. Ilyasil Ghafur; Aditya Dandy Firatama; Alfan Nuris Siddiqi (G-Tech: Jurnal Teknologi Terapan, 2026)
Village offices are essential for the daily functioning of the community, especially in Ketegan Rejoso Pasuruan village. To ensure the development and prosperity of the village, the local government must optimize its efforts. The preparation of the construction budget plan is a key aspect, particularly when it comes to involving the community in the planning process. This research aims to obtain a cost budget plan and project timeline for the renovation of the Ketegan Village Office, ensuring that the development process is structured and organized. The Cost Budget Plan calculations in this study refer to the Unit Price Analysis of Pasuruan City in 2023, as well as a survey of building materials and bestek (technical specifications) drawings provided. The study found that the Ketegan Village Office, a single-story building with an area of 100,75 m², will be in Ketegan Village, Rejoso District, Pasuruan Regency. The total cost required for this construction project is IDR. 173.723.000,00, with the construction scheduled to take 2 months or 60 calendar days, assuming a 7-day workweek. Achieving accurate results requires a comprehensive understanding of all the stages involved in calculating the budget plan.